Interrogating the Links Between Dynasties and Development in the Philippines - Mendoza, Ronald (Archīum Ateneo, 2023)
This article nuances the poverty-inducing effect of political dynasties. We argue that local dynasties in the Philippines can pursue different development trajectories based on their ownership of local businesses and their province's initial state capacity. Adapting a framework developed by Bourguignon and Verdier, we develop a typology of political dynasties that acknowledges heterogeneity in their motivations as well as in the political opportunity structures that they work in. This outlines a theory of change that fosters the necessary conditions for political and economic competition over time, even in areas ruled by political dynasties. While the focus is on the Philippines, research on the nexus between political and economic competition provides insight into issues of political dynasties, competition policy, governance, and accountability faced by a broader set of countries.